Produção de vodca a partir de batata (Solanum tuberosum L.) cultivar ágata - Menezes, Aline Galvão Tavares (2014)
This study was performed with the objective of evaluating the feasibility of using potato pulp for the production of vodka, a distill-rectified alcoholic beverage. The first stage was characterizing the potato pulp, verifying the presence of large amounts of starch, which could be used for obtaining sugars for the alcoholic fermentation. The potato pulp was submitted to different proportions with water and, later, underwent an enzymatic process with two α-amylase enzymes and amyloglucosidase enzyme in different concentrations, varying the time of the second stage of hydrolysis. We verified that the highest concentrations of pulp/water (0.1502 g dry matter/g water), enzyme (6.5 mL/kg of dry matter) and time (11.04 h) resulted in the best treatment condition. The hydrolyzate obtained was used for fermentation into two treatments, first containing only hydrolyzed medium with 11 ºBrix and the second hydrolyzed medium supplemented with sucrose with 17 ºBrix. For both treatments we tested three strains of Saccharomyces cerevisiae yeast, baking pressed yeast, CA11 and CAT1. The yeast was selected due to the higher conversion factor (0.47 g ethanol / g ART), efficiency (89.39 %) and ethanol productivity (5.92 g/Lh). Two consecutive distillations were performed, the first in copper distiller and the second in a glass column. The final alcoholic distillate was diluted with purified water to set the alcohol concentration (36 57% v/v) and was submitted to filtration through commercial activated carbon. Secondary analyzes were performed on the filtered distillate. The analyses showed that the beverage did not fit the established legislation, presenting higher secondary compound sum value (148.33 mg/100 mL anhydrous alcohol) and higher concentration of methanol (35.04 mg/100 mL anhydrous alcohol), fitting the legislation for not presenting copper and for the alcohol content of 39.71 % v/v.